Fiscal policy and national saving in Mexico, 1980-2006 - Cermeño, Rodolfo; Roth, Bernardo D.; Villagómez, F. Alejandro (Estudios Económicos de El Colegio de México, 2008)
This paper uses structural vector autoregression (SVAR) models to characterize the dynamic impact of fiscal policy on national saving. SVARs have extensively been used in case of monetary policy. Data adjusted for inflation, capital flight, the value loss of debt and cyclical effects, is used rather than traditional measures. Our results suggest that fiscal policy that increases the structural surplus has a positive impact on national saving, some negative impact on private savings in shorter horizons but any significant effect over longer horizons, and a negative effect on the output gap.